2018
DOI: 10.1175/jcli-d-18-0237.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Sea Ice Decline Did Not Significantly Increase the Total Liquid Freshwater Content of the Arctic Ocean

Abstract: The freshwater stored in the Arctic Ocean is an important component of the global climate system. Currently the Arctic liquid freshwater content (FWC) has reached a record high since the beginning of the last century. In this study we use numerical simulations to investigate the impact of sea ice decline on the Arctic liquid FWC and its spatial distribution. The global unstructured-mesh ocean general circulation model Finite Element Sea Ice–Ocean Model (FESOM) with 4.5-km horizontal resolution in the Arctic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 84 publications
11
73
0
Order By: Relevance
“…Both OMIP-1 and OMIP-2 simulations show high salinity bias in the Arctic Ocean, with some reduction implied for OMIP-2 simulations. Note that the Arctic Ocean has shown a strong freshening trend over recent decades (Rabe et al, 2014;Wang et al, 2019), thus restoring sea surface salinity to the climatology in the models may result in high salinity biases. The model spread is large in the Arctic Ocean, where the 310 diversity among models in the sea ice processes, the surface vertical mixing processes, and the treatment of salinity restoring can lead to large difference in sea surface salinity.…”
Section: Evaluation Of Contemporary Climate Of the Last Forcing Cyclementioning
confidence: 99%
“…Both OMIP-1 and OMIP-2 simulations show high salinity bias in the Arctic Ocean, with some reduction implied for OMIP-2 simulations. Note that the Arctic Ocean has shown a strong freshening trend over recent decades (Rabe et al, 2014;Wang et al, 2019), thus restoring sea surface salinity to the climatology in the models may result in high salinity biases. The model spread is large in the Arctic Ocean, where the 310 diversity among models in the sea ice processes, the surface vertical mixing processes, and the treatment of salinity restoring can lead to large difference in sea surface salinity.…”
Section: Evaluation Of Contemporary Climate Of the Last Forcing Cyclementioning
confidence: 99%
“…1a), it has been shown that FESOM1.4 performs as well as a variety of coarse structured-mesh ocean models, in terms of modeled general ocean circulation (e.g., Danabasoglu et al, 2016;Wang et al, 2016b, c). The range of medium-sized meshes between 500 and 2000 K surface vertices includes the meshes with either globally increased resolution to a higher extent or locally strongly refined key regions of interest (Wang et al, 2016a(Wang et al, , 2018a(Wang et al, , b, 2019bWekerle et al, 2017;Sein et al, 2016Sein et al, , 2018. Using FESOM1.4, it was shown that this class of meshes is well suited for ocean-only simulations, as well as for fully coupled model simulations, which, however, require sufficiently large amounts of computational resources.…”
Section: Meshes Usedmentioning
confidence: 99%
“…1 left) it has been shown that FESOM1.4 performs as well as a variety of coarse structured mesh ocean models, in terms of modeled general ocean circulation (e.g Danabasoglu et al, 2016;Wang et al, 2016aWang et al, , 2016b. The range of medium-sized meshes between 500K until 2000K surface vertices, includes the meshes with either globally increased resolution to a higher extent or locally strongly refined key regions of interest (Wang et al, 2016(Wang et al, , 2018a(Wang et al, ,b, 2019bWekerle et al 2017;Sein et al 2016Sein et al , 2018. Using FESOM1.4 it was shown that this class of meshes are well suited for ocean only simulations, as well as for fully coupled model simulations, which, however, require sufficiently large amounts of computational resources.…”
Section: Meshes Usedmentioning
confidence: 99%